Davidson on metaphor and conceptual schemes - Kotze, H. B. (Hendrik Benjamin) (Stellenbosch : Stellenbosch University, 2012)
Compilation of two papers, the first of which was accepted for publication in the South African Journal of Philosophy in the second half of 2001.